Effect of Plant Age on Cotton Leaf Curl Disease (CLCuD) in Relation to Environmental Conditions: Cotton Leaf Curl Disease and Weather - Mahmood, Tariq; Tahir, Muhammad; Mahmood, Hafiz Tariq; Hussain, Sabahat; Muhammad, Dil Baugh (Biological Sciences - PJSIR, 2014)